Pengaruh E-Filing, Dan Peran Relawan Pajak Terhadap Kepatuhan Pelaporan SPT Wajib Pajak Pada KPP Lamongan - Cici Avita Sari (Universitas Muhammadiyah Ponorogo, 2025)
The study aims to determine the Effect of E-Filing and Tax Volunteers on Taxpayer SPT Reporting Compliance at the Lamongan Tax Office (KPP) located at Jl. Raya Sunan Giri No. 72, Beringin, Tumenggungan, Lamongan. This study is a survey with quantitative research. The population in this study are Individual Taxpayers who have been registered at the Lamongan KPP. Sampling uses a Purposive Sampling technique and a sample of 100 respondents was obtained using the Slovin formula. Data collection techniques in this study use interviews and questionnaires. Data analysis used is a validity test, reliability test, multiple linear regression analysis, classical assumption test, R2 determination coefficient test, and hypothesis testing through the t test which is used to determine the Effect of E-Filing and the Role of Tax Volunteers partially on Taxpayer SPT Reporting Compliance at the Lamongan KPP. From the analysis results obtained the results of the t-test variable t arithmetic = 3,722 > t_table = 1,290 which states that E-Filing has an effect on Taxpayer SPT Reporting Compliance. The Role of Tax Volunteers variable t arithmetic = 4,695 > t_table = 1,290 which states that the Role of Tax Volunteers has an effect on Taxpayer SPT Reporting Compliance. While the R Square of 0,986 shows that 98,6% of the Taxpayer SPT Reporting Compliance variable is influenced by E-Filing and the Role of Tax Volunteers. While the remaining 1,4% is influenced by other variables not studied. Keywords: E-Filing, The Role Of Tax Volunteers, And Taxpayer SPT Reporting Compliance, Taxpayer Awareness, Taxpayer Compliance.